Immature hemodialysis arteriovenous fistulas: What should we aim for? - Silva,Rui F. (2021)
ABSTRACT Arteriovenous fistulas (AVFs) are the first-choice vascular access for most HD patients. Up to 60% of AVFs do not mature adequately, mostly due to stenosis. Surgical and endovascular techniques can rescue up to 80% of these AVFs from primary failure, allowing them to be safely and effectively used in HD, preserving venous capital, and avoiding placement of CVCs and associated complications. This article reviews and summarizes the existing literature, offering a practical approach on early identification, treatment, and monitoring of immature AVFs.